Acrylamide Formation during the Frying of Beef Burger: Effect of Temperature and Time (Chemical Engineering Research Bulletin, 2011)
Acrylamide (CH2 = CHCONH2) is creating cancer chemical which produced in certain foods due to heating process at high temperature and low humidity conditions. Due to the hazardous effect of acrylamide, in this study, the effect of additives (garlic and pepper), oils (sunflower and Canola), frying temperature (180 and 200°C) and frying time (4 and 6 minutes) on the acrylamide levels has been discussed in fried beef burger using full factorial design of experiment (DOE). Produced acrylamide in each sample was analyzed by FID-GC system in the presence of internal standard. Between investigated parameters, results from DOE reveal that frying temperature has the highest impact on the produced acrylamide.Key words: Acrylamide; frying temperature; frying time; full factorial designDOI: http://dx.doi.org/10.3329/cerb.v15i1.7610 Chemical Engineering Research Bulletin 15 (2011) 39-44